Diffrentiated Learning to Improve Student Competencies - Iim; Suparman; Ika Maryani; Julita Lindriany (Journal of Pedagogy and Education Science, 2026)
Differentiated learning is an instructional approach that customizes learning processes, content, and products according to students' diverse needs, interests, and readiness levels. This approach has emerged as a critical strategy for addressing classroom diversity and optimizing both academic and non-academic competencies. Despite growing interest, a systematic understanding of how differentiated learning enhances student competencies across varied educational contexts remains limited. This study employed a systematic literature review to examine the role of differentiated learning in improving student competencies. A comprehensive search across academic databases identified peer-reviewed articles published between 2015 and 2025. Selected studies underwent thematic analysis to identify implementation patterns, underlying principles, and effectiveness indicators of differentiated learning strategies. The analysis reveals that differentiated learning significantly enhances learning motivation, student engagement, and equitable competency achievement across diverse populations. Three critical success factors emerged: systematic diagnostic assessment to map individual learning needs, teacher flexibility and pedagogical skills in designing adaptive strategies, and robust institutional support for inclusive learning environments. Evidence indicates substantial improvements in both cognitive and affective learning outcomes when differentiation is properly implemented. Effective differentiated learning transcends mere pedagogical technique, requiring continuous professional development, collaborative school culture, and responsive formative assessment practices. The integration of student-centered approaches and ongoing evaluation mechanisms amplifies positive impacts on competency development. However, implementation challenges persist, including time constraints and resource limitations. This study confirms that differentiated learning represents a strategic, evidence-based approach for creating equitable and adaptive learning processes that sustainably improve student competencies across diverse educational settings.